Cooling characteristics of solar photovoltaic panels based on phase change materials. (January 2023) - Xu, Zhiming; Kong, Qinglu; Qu, Hongwei; Wang, Chong
Abstract: The efficiency of photovoltaic(PV) panels decreases as their temperature increases, so effective cooling of them is necessary. The cooling of PV panels based on phase change materials(PCMs) is an emerging cooling method that has recently received the attention of scholars around the world. Herein, the cooling characteristics of PCM on PV panels are experimentally investigated to study the cooling effect of PCM on solar PV panel cooling technology (PV-PCM) and explore the effect of inverse process of PCM from molten to solidified state on the temperature of solar PV panels after cooling. The results reveal that the PCM can effectively reduce the temperature of solar PV panels under the condition of no wind, irradiance of 1000 W/m 2 and ambient temperature of 7.3 °C. The PCM can reduce the average temperature of the upper and back surfaces of solar PV panels by 33.94 °C and 36.51 °C within 300 min, respectively. Moreover, the PCM increased the average maximum power generation efficiency of solar PV panels by 1.63% and the average maximum output power by 1.35 W. The solar PV panels cooled without PCM took only 60 min to cool from the maximum temperature to room temperature, whereas the solar PV panels in PV-PCM system took 480 min to cool down to room temperature.